Moderasi, Perdamaian dan Toleransi dalam Hadis - Zahri, Ahmad Fauzan; Nabilah, Is'ad Durrotun; Ilmi, Moh. Hudal Hafid; Razi, Fahrur; Rizaka, Maghza (State Islamic University of Datokarama Palu, 2024)
Moderation, peace and tolerance are core teachings of Islam that are explained in many religious texts. Aḥmad al-Ṭayyib explained several hadiths related to moderation, peace and tolerance in several of his books and speeches. This study aims to discuss the thoughts of Aḥmad al-Ṭayyib regarding the hadiths of moderation, peace and tolerance. This research uses qualitative research with library research method. The results of the study state that Islamic moderation teaches humans to provide freedom and independence and equal rights for women, and not to discriminate among fellow human beings. Then to maintain peace between humans, a sense of security should be created and there should be no attitude of fear or threat to others. Tolerance between religions is also needed to create a sense of peace, one of which is by allowing people to choose their religion and not forcing them to convert to Islam.